Age and tectonic significance of the Louth Volcanics: implications for the evolution of the Tasmanides of eastern Australia - Dwyer, R.; Collins, Bill; Hack, A.; Hegarty, R.; Huang, H. (Taylor & Francis Co Ltd, 2018)
© 2018 Geological Society of Australia Re-evaluation of geochemical and geophysical datasets, and analysis of magmatic and detrital zircons from drill-core samples extracted from the Louth region of the southern Thomson Orogen (STO), augmented by limited field samples, has shown that two temporally and compositionally distinct igneous groups exist. The older Lower Devonian, calc-alkaline group corresponds to complexly folded, high-intensity curvilinear magnetic anomalies in the Louth region (Louth Volcanics) and are probable equivalents to Lower Devonian volcanics in the northern Lachlan Orogen. A younger Permo-Triassic alkaline assemblage forms part of an E–W corridor of diatremes that appears to relate to focussed lithospheric extension associated with the later stages of the Hunter–Bowen Orogeny in the New England Orogen. The alkaline group includes gabbros previously considered as Neoproterozoic, but all magmatic rocks, including alkaline basalts, contain an unusual number of xenocrystic zircons. The age spectra of the xenocrystic zircons mimic detrital zircons from Cobar Basin sedimentary rocks and/or underlying Ordovician turbidites, suggesting incorporation of upper crustal zircons into the alkaline basaltic magmas. A distinct difference of detrital zircon age spectra from central Thomson Orogen metasediments indicates the STO metasediments have greater affinities to the Lachlan Orogen, but both orogens probably began in the Early Ordovician during widespread backarc extension and deposition of turbidites in the Tasmanides. A surprising result is that Ordovician, Devonian and Permo-Triassic basaltic rocks from the STO and elsewhere in the Tasmanides, all yield the same Nd-model ages of ca 960–830 Ma, suggesting that Neoproterozoic subcontinental lithospheric mantle persisted throughout the evolution of the Tasmanide orogenic system.